Engineering Hybrid Learning Communities: The Case of a Regional Parent Community - Sven Strickroth; Niels Pinkwart (Systems, 2014)
We present an approach (and a corresponding system design) for supporting regionally bound hybrid learning communities (i.e., communities which combine traditional face-to-face elements with web based media such as online community platforms, e-mail and SMS newsletters). The goal of the example community used to illustrate the approach was to support and motivate (especially hard-to-reach underprivileged) parents in the education of their young children. The article describes the design process used and the challenges faced during the socio-technical system design. An analysis of the community over more than one year indicates that the hybrid approach works better than the two separated “traditional” approaches separately. Synergy effects like advertising effects from the offline trainings for the online platform and vice versa occurred and regular newsletters turned out to have a noticeable effect on the community.